Documenting first wave feminisms. - Forestell, Nancy M. (Nancy Margaret), 1960-; Moynagh, Maureen Anne, 1963- (Studies in gender and history., 2012)
Using primary documents dating from the abolitionist movement to the Second World War, Maureen Moynagh and Nancy Forestell investigate the tensions inherent in organizing early transnational feminist movements.